Towards an ontology for open source software development - Simmons, Gregory; Dillon, Tharam S. (Springer-Verlag, 2006)
Software development is a knowledge intensive process and the information generated in open source software development projects is typically housed in a central Internet repository. Open source repositories typically contains vast amounts of information, much of it unstructured, meaning that even if a question has previously been discussed and dealt with it is not a trivial task to locate it. This can lead to rework and confusion amongst developers and possibly deter new developers from getting involved in the project in the first place. This paper will present the case for an open source software development ontology. Such an ontology would enable better categorization of information and the development of sophisticated knowledge portals in order to better organize community knowledge and increase efficiency in the open source development process.